Online PR Dictionary – Interview with Péter János Sós - Balogh, Gábor (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2024)
Do we know what CCP, deep fake, NFT, or SEO are? What do USP and EVP mean in PR and communication management in general? What is the difference between a brand representative and a brand ambassador? Who are the biggest names in PR? The answers can be found in a groundbreaking publication, the PR dictionary, which contains more than 370 entries in 12 subject areas (e.g., lobbying, media, branding, the digital world, indicators).The purpose of the dictionary is to clarify the basic concepts of PR, marketing, and advertising. In addition to clarifying the meaning of words, the publication also aims to ensure that professionals have a uniform understanding of each term and that university students and young professionals can navigate the language and foreign terminology of the communications and PR professions.